네오니코티노이드계 4종 농약의 서양뒤영벌 급성 접촉 및 섭식 독성평가 - 김아름누리; Areumnuri Kim; 김보선; Boseon Kim; 전경미; Kyongmi Chon; 이환; Hwan Lee; 박연기; Yeon-ki Park; 유아선; Are-sun You; et al. (Hanguk hwangyeong nonghak hoeji, 2020)
BACKGROUND: Bumblebees have been shown to be very effective pollinators for most greenhouse tomatoes. Neonicotinoid insecticides are one of the most widely used pesticides in tomato crops in Korea. METHODS AND RESULTS: This study was carried out to investigate the toxicity of four neonicotinoid insecticides (clothianidin, dinotefuran, imidacloprid and thiamethoxam) to bumblebees based on the OECD guidelines (No.246, 247). The 48 hr LD 50 (μg a.i. /bumblebee) values in the acute contact toxicity tests were determined as follows: clothianidin, 0.467; dinotefuran, 3.741; imidacloprid, 3.967; and thiamethoxam, 0.747. The 48 hr LD 50 values in the acute oral toxicity tests were determined as follows: clothianidin, 0.005; dinotefuran, 0.056; imidacloprid, 0.325; and thiamethoxam, 0.018. The acute contact and oral toxicity of the test insecticides to bumblebees from most to least toxic was clothianidin > thiamethoxam > dinotefuran > imidacloprid. CONCLUSION: This study provided the basic toxicological data of neonicotinoid insecticides for bumblebees. In the near future, acute toxicity and mixture toxicity of other pesticides to bumblebees could be determined using this method.